SOCIAL MEDIA IN INTERNATIONAL BRAND COMMUNICATION OF SMES - A multiple case study of small Finnish design-intensive companies - Kuitunen, Karita (My University, 2012)
Social media is a rather new phenomenon which has revolutionised the world of online communication. However, academic research on how companies can benefit from social media is lacking. The research objective of this thesis was to examine the use of social media in international brand communication of small Finnish design-intensive companies. Therefore, this research contributes also to the research gap in SME branding. The focus was on communication targeted at consumers. The research was carried out as a mixed methods research employing the questionnaire and multiple case study methods. The questionnaire was used to gather preliminary information on Finnish design-intensive companies and to provide an eligible list of companies for deeper examination. Then, four case companies were studied in more depth. The empirical evidence of the case companies was mainly gathered through theme interviews. The results of the questionnaire shed light on the internationalisation of small Finnish designintensive companies. On average, the companies had internationalised rather quickly after they had been founded. However, the share of exports was rather low in most of the companies. The results revealed also that social media was already used widely in the exporting companies and the use can be expected to grow in future. The findings of the multiple case study suggest that branding activities in small Finnish designintensive companies are constrained by limited resources and skills. In addition, the branding activities are strongly guided by the vision and values of the entrepreneur(s) rather than extensive marketing research. The brand structure was simple in all case companies and they aimed at having a standardised brand image across markets. However, all case companies had faced a need for some adaptation of their international brand communication. Internationally important brand communication channels were international fairs, the internet, word-of-mouth and social media. Social media offered a cost-effective brand communication channel for the case companies. It was used for various purposes, such as creating brand awareness and affecting how the brand is perceived. The entrepreneurs found the use of social media to be rather easy and the case companies had not faced any major challenges. However, the companies had recognised that communication in social media requires consistency and planning. The planning was rather informal and stayed on a general level. Overall, the utilisation of social media in the case companies was limited by a lack of resources. It seemed to affect especially the follow-up of brand communication in social media which stayed rather superficial.